BIM technology application in construction industry of Vietnam - Hieu, Le Trung; Dat, Nguyen Van; Hung, Ngo Xuan (Vestnik Tomskogo gosudarstvennogo arkhitekturno-stroitelʹnogo universiteta, 2024)
In Vietnam, the concept of building information modeling (BIM) has become quite popular in the construction industry. The BIM application optimizes the information exchange and coordination between participants in various project, helps to visualize design, construction and project management processes, ensures the project quality and various benefits at a later stage of the project management and operation. Purpose: A review of the current situation and trends of BIM application in construction investment projects as well as inevitable digital transformation in the construction sector of Vietnam. Methodology: Statistical and comparative-historical methods, survey data obtained through a questionnaire in the form of statistical analysis using charts describing the BIM application in the construction industry in Vietnam. Research findings: It is shown that BIM is mostly used by enterprises that directly benefit from modern technologies. The BIM reflects the diversity of research subjects, as is can be applied at different stages by many project stakeholders. It is found that many surveys are distributed rather evenly, confirming that all key project participants are interested in using BIM. Originality: This study supplements information on the current status and trends of the BIM application in construction investment projects in different countries, including Vietnam. Thus, the BIM is increasingly being used in the construction industry, but there is still a lack in qualified personnel who can use this technology.